The limits of religious freedom in Indonesia: with reference to the first pillar Ketuhanan Yang Maha Esa of Pancasila - Abdul Mu'ti; Ahmad Najib Burhani (Indonesian Journal of Islam and Muslim Societies, 2019)
Surveys and researches have indicated various factors leading to or instigating the rise of religious intolerance in Indonesia after the Reformasi in 1998. This study, however, aims to see intolerance and discrimination as something embedded in Indonesian ideology, i.e. Pancasila, which seems to be lacking in previous studies, including the studies on the connection between Pancasila and discriminative regulations implemented is several districts and provinces in Indonesia. The questions dealt with in this paper are the following: Why did religious radical groups able to exert their influence to the government and moderate Muslim majority in treating minorities? What are, if any, the constitutional and legal limits of religious freedom in Indonesia? This paper aims to scrutinize constitutional and legal documents, including the first pillar of Pancasila, to find their shortcomings in protecting religious freedom. This paper argues that Pancasila has set Indonesia into religiously monotheistic state, which provided the government the necessary tool to force non-theistic, polytheistic, and non-monotheistic religions to modify their theological beliefs in order to be accepted as recognized or official religions. Pancasila also justifies the existence of favoritism to certain religions deemed fit to this ideology. Berbagai survei dan penelitian telah menunjukkan berbagai faktor yang menyebabkan atau memicu bangkitnya intoleransi beragama di Indonesia setelah Reformasi tahun 1998. Penelitian ini ingin melihat intoleransi dan diskriminasi sebagai sesuatu yang secara tak sadar tertanam dalam ideologi Indonesia, yaitu Pancasila. Tema ini tampaknya kurang menjadi perhatian dalam studi sebelumnya, termasuk studi tentang hubungan antara Pancasila dan peraturan diskriminatif yang diterapkan di beberapa kabupaten dan provinsi di Indonesia. Pertanyaan yang dibahas dalam artikel ini diantaranya adalah: Mengapa kelompok-kelompok radikal keagamaan dapat mempengaruhi pemerintah dan mayoritas umat Muslim yang moderat dalam bersikap terhadap kelompok minoritas? Apa, jika ada, batasan konstitusional dan legal kebebasan beragama di Indonesia? Artikel ini bertujuan untuk meneliti dokumen dokumen konstitusional dan hukum, termasuk pilar pertama Pancasila, untuk menemukan kekurangan dalam melindungi kebebasan beragama. Artikel ini berargumen bahwa Pancasila telah menetapkan Indonesia menjadi negara monoteistik religius, yang memberikan pemerintah piranti yang diperlukan untuk memaksa agama-agama non-teistik, politeistis, dan non-monoteistik untuk memodifikasi keyakinan teologis mereka agar diterima sebagai agama yang diakui atau resmi. Pancasila juga membenarkan keberadaan favoritisme untuk agama-agama tertentu yang dianggap cocok dengan ideologi ini.